Clinical predictors of response and discontinuation of belimumab in patients with systemic lupus erythematosus in real life setting. Results of a large, multicentric, nationwide study. (January 2018) - Iaccarino, Luca; Andreoli, Laura; Bocci, Elena Bartoloni; Bortoluzzi, Alessandra; Ceccarelli, Fulvia; Conti, Fabrizio; De Angelis, Rossella; De Marchi, Ginevra; De Vita, Salvatore; Di Matteo, Andrea; Emmi, Giacomo; Emmi, Lorenzo; et al.
Abstract: Objective: To investigate efficacy, safety and survival of belimumab and to identify predictors of drug response and drug discontinuation in patients with active SLE in clinical practice. Patients and methods: Data of SLE patients, treated with belimumab, from 11 Italian prospective cohorts were analyzed. SLEDAI-2K, anti-dsDNA, C3, C4, prednisone daily dose, DAS-28, 24-h proteinuria, CLASIa (Cutaneous LE Disease Area and Severity Index Activity) were recorded at baseline and every 6 months. SLE Responder Index-4 (SRI-4) was calculated at 12 and 24 months. Demographic and clinical features and comorbidities were included in the univariate and multivariate analysis. Adverse events were recorded at each visit. Statistics was performed using the SPSS software. Results: We studied 188 SLE patients, mean follow-up 17.5 ± 10.6 months. The most frequent manifestations, which required the use of belimumab, were polyarthritis (45.2%) and skin rashes (25.5%). SRI-4 was achieved by 77.0% and 68.7% of patients at 12 and 24-months. Independent predictors of 12-month response were SLEDAI-2K ≥ 10 (OR 40.46, p = 0.001) and polyarthritis (OR 12.64, p = 0.001) and of 24-month response were SLEDAI-2K ≥ 10 (OR 15.97, p = 0.008), polyarthritis (OR 32.36, p = 0.006), and prednisone ≥7.5 mg/day (OR 9.94, p = 0.026). We observed a low rate of severe adverse events. Fifty-eight patients (30.8%) discontinued belimumab after a mean follow-up of 10.4 ± 7.5 months. The drug survival was 86.9%, 76.9%, 69.4%, 67.1%, and 61.9% at 6, 12, 18, 24, and 30 months, respectively. No factors associated with drug discontinuation were found. Conclusion: Belimumab is effective and safe when used in clinical practice setting. Highlights: This is a large nationwide cohort of patients followed in real life setting. Belimumab reduces disease activity, prednisone intake and lupus flares. Belimumab hinders the expected damage progression in patients with lupus. Predictors of response were SLEDAI-2K ≥ 10, polyarthritis and prednisone ≥7.5 mg/die. Drug survival is similar to TNF inhibitors in patients with rheumatoid arthritis.